2007
DOI: 10.1097/phm.0b013e31805c00a1
|View full text |Cite
|
Sign up to set email alerts
|

Adapting Multiple-Family Group Treatment for Brain and Spinal Cord Injury Intervention Development and Preliminary Outcomes

Abstract: The findings support the adaptation of MFGT for brain and spinal cord injuries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
44
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(49 citation statements)
references
References 42 publications
(32 reference statements)
5
44
0
Order By: Relevance
“…Training programs focusing on the individuals' resourcefulness and mechanisms of selfcontrol, as well as family func tioning, are promising ways to promote psycholog ical wellbeing. Previous studies have shown that activities that increase selfesteem (Yagmurlu, Yag murlu, & Yilmaz, 2009) and interventions targeting copingeffectiveness for both the affected individuals (e.g., Kennedy, Duff, Evans, & Beedie, 2003) and their families (e.g., Rodgers et al, 2007) contribute signifi cantly to improvements in their problemsolving skills, adjustment to disability, and lowering depres sive feelings, while also promoting family harmony. Our results suggest that interventions which pro mote the resources of the individuals with disability and their caregivers, as well as promoting a positive family environment, may help minimize the depres sive feelings of individuals with orthopedic disability.…”
Section: Discussionmentioning
confidence: 99%
“…Training programs focusing on the individuals' resourcefulness and mechanisms of selfcontrol, as well as family func tioning, are promising ways to promote psycholog ical wellbeing. Previous studies have shown that activities that increase selfesteem (Yagmurlu, Yag murlu, & Yilmaz, 2009) and interventions targeting copingeffectiveness for both the affected individuals (e.g., Kennedy, Duff, Evans, & Beedie, 2003) and their families (e.g., Rodgers et al, 2007) contribute signifi cantly to improvements in their problemsolving skills, adjustment to disability, and lowering depres sive feelings, while also promoting family harmony. Our results suggest that interventions which pro mote the resources of the individuals with disability and their caregivers, as well as promoting a positive family environment, may help minimize the depres sive feelings of individuals with orthopedic disability.…”
Section: Discussionmentioning
confidence: 99%
“…Family members were interested in how the treatment affects the progress of both rehabilitation and recovery. Family members also sought information about the patient's medical treatment (Arango-Lasprilla et al, 2010;McCabe et al, 2007;Murray, Maslany, & Jeffery, 2006;Rodgers et al, 2007;Wongvatunyu & Porter, 2005). Family members needed to be reassured that the patient was receiving the best possible care.…”
Section: Figure 1 Data Review and Inclusion And Exclusion Criteria Fimentioning
confidence: 99%
“…MFG has been found to improve the management of other psychiatric and neurological conditions (e.g., schizophrenia, traumatic brain injury) and decrease health care usage (Dyck et al, 2002;McFarlane, 2002;McFarlane, Link, Dushay, Marchal, & Crilly, 1995;Rodgers et al, 2007). In this intervention, we modified the standard MFG format of McFarlane (2002) to include formalized training in cognitive rehabilitation strategies.…”
Section: Introductionmentioning
confidence: 99%